KEMAMPUAN REGULASI EMOSI PADA GURU ANAK BERKEBUTUHAN KHUSUS DI SLB AL-CHUSNAINI SIDOARJO - Pambayun, Sekar Putri (JPI (Jurnal Pendidikan Inklusi), 2023)
Teachers who handle special need students good emotional regulation skills. This is intended so that teachers do not get dragged into negative emotions. This research was conducted to explore how special school teachers regulate their emotions in dealing with difficult situations and conditions every day. As well as analyzing the efforts made by SLB teachers to strengthen emotional regulation abilities using Thompson's theory. This research was conducted using a phenomenological approach with descriptive qualitative methods. The findings of this research show that in Thompson's theory of emotional regulation, both participants performed well in three aspects: monitoring, evaluating, and modifying emotions. The study's findings indicate that both participants already have a strong understanding of emotional control, thus they have no issue interacting with students with special needs.Keywords: Emotion regulation, SLB Teacher, special needs children